The role of architecture in the bicentennial - Nieva Villegas, Mayda Alvina (2021)
This reflective proposal is aimed at conscious citizens that we want architecture to play a leading role in the substantive changes in the organization of urban space in city planning as we are rapidly approaching the bicentennial of our country. The research design is of a mixed, descriptive-comparative type, due to the degradation, deterioration, destruction and alteration that our cities are suffering; and it has a qualitative approach. The cities at the present time are going through a crisis and degradation of their monumental architectural heritage, to this is added the mismanagement of municipal administrations in terms of urban development and misuse of regulations conspiring with the essence of contemporary thought in their production creative for the development of cities. Citizens do not feel that there are substantial changes for a better coexistence. In 1921 in the Centennial the slogan was "new man" in the 1971 sesquicentennial "the popular power", at the present time it is called "Year of the Bicentennial of Peru: 200 years of Independence" but no change is noticed that is felt the independence. People need a change in architecture as a result of pandemic moments and that architectural objects must provide physical, psychological, spiritual satisfaction so that citizens can fulfill the main activity of habitability and socialization in its maximum dimension of comfort given to that spaces are fragmented and do not fulfill their function; so we must revalue contemporary architecture, which implies a constant rediscovery of fundamental human qualities transferred to architectural and urban space.